X69R Is a Non-Essential Gene That, When Deleted from African Swine Fever, Does Not Affect Virulence in Swine - Elizabeth Ramirez-Medina; Elizabeth Vuono; Sarah Pruitt; Ayushi Rai; Ediane Silva; James Zhu; Lauro Velazquez-Salinas; Douglas P. Gladue; Manuel V. Borca (Viruses, 2020)
African swine fever virus (ASFV) is currently causing devastating outbreaks in Asia and Europe, and the ASFV strain Georgia (ASFV-G) is responsible for these outbreaks. ASFV-G is highly virulent and continues to be maintained in these outbreak areas, apparently without suffering significant genomic or phenotypic changes. When comparing the genome of ASFV-G to other isolates, a thus-far uncharacterized gene, X69R, is highly conserved and, interestingly, is similar to another ASFV uncharacterized gene, J64R. All sequenced ASFV isolates have one or both of these genes, X69R or J64R, suggesting that the presence of at least one of these genes may be necessary for ASFV replication and or virulence. The X69R gene is present in the ASFV-G genome while J64R is absent. To assess the importance of X69R in ASFV-G functionality, we developed a recombinant virus by deleting the X69R gene from the ASFV-G genome (ASFV-G-ΔX69R). ASFV-G-ΔX69R had the same replication kinetics in primary swine macrophage cultures as the parental ASFV-G, indicating that the X69R gene is not essential for ASFV-G viability or efficient replication in the main target cell during in vivo infection. In addition, swine intramuscularly inoculated with a low dose (102 HAD50) of ASFV-G-ΔX69R developed a clinical disease indistinguishable from that induced by the same dose of the virulent parental ASFV-G isolate. Viremia values of ASFV-G-ΔX69R did not significantly differ from those detected in animals infected with parental virus. Therefore, deletion of the X69R gene from ASFV-G does not affect virus replication or virulence in swine.